Role of a Checklist to Improve Patient Safety in Interventional Radiology - Soumil Singhal; Mangerira Chinnappa Uthappa (Journal of Clinical Interventional Radiology ISVIR)
A checklist can be defined as a comprehensive formal list of essential actions to be taken in a specific fashion. This concept has been extended from the aviation industry to health care to improve patient outcome and patient satisfaction with a significant reduction in complication rates. This review article aims to assess the importance and benefits associated with the use of a well-formulated checklist while performing the various minimally invasive image-guided procedures. Various databases including PubMed, Medline, Scopus, and Cochrane were searched for using various keywords including “Checklist,” “Radiology,” “Interventional Radiology,” “Image-Guided Procedure,” and “minimally invasive procedure.” The use of a checklist is the way ahead especially when patients today require minimal risk but demand high-quality care. Implementation of such an easy-to-perform tailor-made mechanism can significantly improve patient outcome and patient satisfaction.